Polymorphism in the SREBP-1 gene is associated with milk production traits of Jersey cattle - PROSKURA, WITOLD STANIS£AW; DYBUS, ANDRZEJ; ZABORSKI, DANIEL; SOBEK, ZBIGNIEW; YU, YU-HSIANG; CHENG, YEONG-HSIANG (The Indian Journal of Animal Sciences, 2017)
The sterol regulatory element-binding protein-1 (SREBP- 1) gene has been indicated to be linked to milk production traits in cattle, especially to milk fat yield and fatty acid composition. The transcription factor encoded by this gene is involved in the regulation of fat metabolism, so it is supposed that the variability of the SREBP-1 gene could influence these traits. The aim of this study was to analyze the association between the 84-bp insertion/deletion polymorphism of the SREBP-1 gene and milk production traits in Jersey cattle. The study found significant associations of the SREBP-1 gene polymorphism with fat content in the first lactation and protein content in the first three lactations analyzed both individually and together. In all cases, the LL genotype was linked to the higher value of the analyzed traits.